Case report: Visual snow as the presenting symptom in multiple evanescent white dot syndrome. Two case reports and literature review - Hang, Chenyue; Yan, Yan (Frontiers in Neurology, 2022)
Purpose: Multiple evanescent white dot syndrome (MEWDS) usually manifests as photopsia, enlarged blind spots, scotomas, and blurred vision. Visual snow and chromatopsia were rarely reported in these patients. Herein, we described two Chinese females with MEWDS who initially presented with visual snow, and one of them also had yellow-tinged vision. Methods: First, we performed the chart review of two patients. Secondly, we reviewed the English literature for all cases of MEWDS through PubMed until December 2021, using the terms “MEWDS” or “multiple evanescent white dot syndrome”. We concluded on all the reported patients’ demographic features and symptoms. The visual acuity of patients with/without positive or negative visual phenomena were compared through One-way ANOVA. Results: Patient 1: A 27-year-old Chinese female experienced continuous visual snow and yellow-tinged vision in the right eye for a week. She noticed tiny white and black dots involving the entire visual field and shimmering light inferiorly. Patient 2: A 22-year-old Chinese female complained of a gray area with continuous visual snow in the temporal visual field of the left eye for 5 days. The ocular examinations, including fundus autofluorescence (FAF), optical coherence tomography (OCT), and indocyanine green angiography (ICGA), confirmed the diagnosis of MEWDS. Their symptoms resolved spontaneously without treatment. We found 60 MEWDS case reports (147 cases) in PubMed. The mean age was 31.2 years old. The mean LogMAR best-corrected visual acuity was 0.35 ± 0.39 at the first visit and 0.01 ± 0.16 at the last visit. The most common symptoms included blurred vision (72.8%), enlarged blind spot (42.2%), photopsia (37.4%), and scotoma (33.3%). Four cases similar to visual snow were discovered. Compared to the patients without visual snow, the patients with visual snow tend to have a larger proportion of females (p = 0.005) and a better visual acuity at the first visit (p = 0.007). Conclusions: Herein, we expand upon the clinical manifestations of MEWDS with visual snow, and the symptoms attributable to visual snow could precede the onset of MEWDS . Neurologists and ophthalmologists should carefully rule out occult chorioretinopathies before diagnosing visual snow syndrome.